2006
DOI: 10.1103/physrevb.73.134101
|View full text |Cite
|
Sign up to set email alerts
|

Transition pressures and enthalpy barriers for the cubic diamondβ-tin transition in Si and Ge under nonhydrostatic conditions

Abstract: We present an ab-initio study of the phase transition cd→β-tin in Si and Ge under hydrostatic and non-hydrostatic pressure. For this purpose we have developed a new method to calculate the influence of non-hydrostatic pressure components not only on the transition pressure but also on the enthalpy barriers between the phases. We find good agreement with available experimental and other theoretical data. The calculations have been performed using the plane-wave pseudopotential approach to the density-functional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 74 publications
8
30
1
Order By: Relevance
“…Nanoindentation studies with various indenter-shapes 2 have shown that non-hydrostatic conditions lower the transformation stress, which is in accordance with theoretical considerations by Gilman (1993a) as well as various atomistic studies (cf. Lee et al, 1997;Cheng et al, 2001;Cheng, 2003;Gaál-Nagy and Strauch, 2006), which suggest a linear relationship between the transformation pressure p and applied von Mises equivalent stress S q := √ 3 /2 S . Transformation events during unloading appear on the force-displacement (P−h) curve (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoindentation studies with various indenter-shapes 2 have shown that non-hydrostatic conditions lower the transformation stress, which is in accordance with theoretical considerations by Gilman (1993a) as well as various atomistic studies (cf. Lee et al, 1997;Cheng et al, 2001;Cheng, 2003;Gaál-Nagy and Strauch, 2006), which suggest a linear relationship between the transformation pressure p and applied von Mises equivalent stress S q := √ 3 /2 S . Transformation events during unloading appear on the force-displacement (P−h) curve (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This choice reproduces the experimentally observed phase transition under hydrostatic compression (Hu et al, 1986), without predicting transformations in hydrostatic tension. Further, the linear relationship between equivalent stress S q and pressure p on the limit surface suggested by MD simulations (Cheng et al, 2001;Cheng, 2003;Gaál-Nagy and Strauch, 2006;Lee et al, 1997) can be smoothly approximated with an arbitrary order of accuracy. The corresponding flow potential is also chosen to be a hyperboloid of revolution, albeit not necessary the same one.…”
Section: Ld-si → Hd-simentioning
confidence: 99%
“…The linear coefficient is similar for all three functionals and close to the values determined previously for the LDA and PW91 functional. 17,18 Considering that the mechanical strength of silicon under uniaxial compression at ambient conditions is about 7 GPa, 58 it may be reasonable to assume that deviatory stresses on the order of 0.5 GPa could be present in the diamond-anvil cell experiments with a pressure medium and even larger deviatory stresses without a pressure medium. This would lower the observed transition pressure by 1.2 GPa compared to perfect hydrostatic compression.…”
Section: Effect Of Stress Anisotropy On the Transition Pressurementioning
confidence: 99%
“…Stress anisotropy in the sample can lower the transition pressure by stabilizing the ␤-Sn phase over the diamond phase. 17,18 We determine the effect of nonhydrostatic stresses on the transition pressure following the approach by Cheng et al 17 The phase transformation from the diamond to the ␤-Sn phase occurs when…”
Section: Effect Of Stress Anisotropy On the Transition Pressurementioning
confidence: 99%
See 1 more Smart Citation